Touring An Other’s Reality: Aboriginals, Immigrants, and Autochromes - Skidmore, Colleen (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2004)
AbstractIn the summer of 1914, a North American Aboriginal family and a German immigrant photographer made (and left) a record of their encounter on the bank of the North Saskatchewan River in Edmonton, Alberta. It took the form of two 5x7 inch autochromes ¾ colour glass-plate transparencies. This paper explores how the fragile autochromes render visible rare views of the historical space shared by the Aboriginal family and the immigrant photographer for whom room was made by treaty. No matter the viewpoint from which they are examined, the images are found to present the story Euro-colonialist culture was telling about itself, a story in which both Aboriginals and immigrants were integral. Today, it is argued, these autochromes mark what was seen when an immigrant and the internally displaced met, and held, one another’s gaze.